Penguatan UMK Melalui Legalisasi Usaha Dan Sertifikasi Halal Di Desa Tembeling - Muhamad Wahyudin; Faiz Faricha; Sholikin; Imam Fatoni (Impact: Jurnal Pengabdian kepada Masyarakat, 2025)
Stunting in Indonesia is still a serious challenge, and although the prevalence rate shows a downward trend, the national target of 14.2% in 2029 (Ministry of Health 2025) has not been achieved. Effective intervention through the Posyandu as the front line is crucial. This study aims to analyze the effectiveness of balanced nutrition education through Posyandu in stunting prevention and identify the success factors of intervention in Temulus Village, Randublatung. The type of research used is Participatory Action Research (PAR), emphasizing active community involvement. The main data sources were obtained from mothers of toddlers, Posyandu cadres, and village health workers as informants and perpetrators. The results showed that educational interventions resulted in a significant increase in the average knowledge score of mothers under five (from 65.5 ± 8.2 to 91.7 ± 4.5 ) and a positive change in feeding behavior (PMBA), evidenced by the increase in MP-ASI practice adherence from 51.1% to 85.5% . In addition, there is a strengthening of cadre capacity through integrated training, which increases their self-efficacy and skills. This participatory education has proven to be effective in bridging the gap between knowledge and practice, as well as significantly contributing to the trend of reducing local stunting risk, affirming the role of Posyandu as a center for sustainable and empowering interventions.